Retrospective evaluation of single patient investigational new drug (IND) requests in pediatric oncology. (9th March 2021) - Shulman, David S.; Kiwinda, Lulla V.; Edwards, Stacey; Clinton, Catherine M.; Hunt, Sarah; Greenspan, Lianne; Lawler, Kristen D.; Reaman, Gregory; Al‐Sayegh, Hasan; Bona, Kira; O'Neill, Allison F.; Shusterman, Suzanne; et al.
Abstract: Background: Single patient Investigational New Drug (IND) applications are one mechanism through which experimental therapies are accessed for children with cancer. The landscape of use, outcomes, and toxicity from single patient INDs remains unknown in pediatric oncology. Methods: We performed a retrospective analysis of all single patient INDs requested and prescribed at a single institution between 1/1/2007 and 5/1/2019. We report aggregate data from the US Food and Drug Administration (FDA) on single patient IND applications over the final two years of the study (2017–2019). We report an overview of all IND applications, as well as clinical descriptions of patients, treatments, outcomes, and toxicity. Results: Over the 2‐year period, the FDA approved all 171 submitted single patient IND requests for pediatric oncology. We identified 56 requests from our center during the 12‐year study period, and all were approved (median time from FDA submission to approval: 1 day (range 0–12)). 71% of requests were based on disease histology. Lack of pediatric clinical trial (65%) was the most common reason for use. 48 approved requests were ultimately administered. The median duration of treatment was 84 days (range: 4–1590), with 3 patients remaining on treatment at time of analysis. Only 7% discontinued treatment due to toxicity. Three‐year overall survival was 50% (95% CI, 35–64). Conclusions: Single patient INDs in pediatric oncology were universally approved in our national and single‐center analysis. In our cohort, single patient INDs were primarily utilized based on disease histology, rather than genomics, for agents that lacked a clinical trial. Abstract : Single patient Investigational New Drug (IND) applications in pediatric oncology are universally approved in a timely fashion in our analysis. Single patient IND therapy is pursued for a range of reasons, with few patients discontinuing therapy due to toxicity.